Evaluation of Determinative Precautions of Unemployment, Undertaken Decisions and Policies to its Decrease in Albania - Terpollari, Arben; Kadiu, Edmond; Apostoli, Stilian; Belegu, Majlinda; Themelko, Henrieta; Merko, Flora (European Journal of Sustainable Development, 2014)
This material is an introduction of the main indicators having affected unemployment and job market, it is a theoretical and empirical analysis of different active policies of employment. The data used in this empirical analysis are observed during the last 15 years. Unemployment, is known as a macroeconomic “chronic disease” to which adding inflation, make up the two most determinative problems in economy. Often; the decrease of unemployment data is considered as the first symptom of the first phase of recession, making it a big financial burden to the government. Unemployment causes discredit of the human capital simultaneously it credits unemployed. Due to this fact, these categories except of being a financial burden to the government, they become a target of risk. (Increase of criminal cases in state level). Albania is the 5th ranked in the region, after Macedonia (33%), Bosnia Herzegovina (24%), Serbia (17.4%) and Turkey (14%), Albania (13%), Montenegro (11%), Greece (9.4%), and Croatia (9.2%). Based on a time limit analysis, we can see that Montenegro has an extreme decrease of unemployment during last 10 years. Unemployment increase is the crucial factor which highly indicates in the average salaries, however, there’s chance of being optimistic to the consumers because of the highly evaluated expectancies. “Expectancies for the 6 upcoming months are foreseen optimistic compared to the last of 2014, the actual balance has decreased in 5.4 points (the balance decrease shows the tendency in lower level of unemployment)”, this is highly emphasized in the report of the Bank of Albania “ Observation of business and consumer’s faith”. Key words: unemployment level, employment policies, unemployment cost, measuring unemployment.